International law and politics: key documents - "Scott,Shirley V. (ed.)" (New Delhi, 2008)
Unique in its breadth of coverage, this carefully designed collection presents the key documents of international law at the global level. The collection encompasses the full spectrum of central issues, with the documents grouped in eight subject areas
Keywords: International law